A single dose of pre‐operative pregabalin reduces post‐operative opioid use after orthotopic liver transplantation. Issue 7 (2nd May 2021) - Knorr, John P.; Barlow, Ashley; Reinaker, Travis S.; Zaki, Radi F.
Abstract: Multimodal pain management strategies including pregabalin (PGB) have been shown to reduce pain and opioid use after many types of surgeries. This was a single‐center, retrospective study aimed to determine whether a single pre‐operative dose of PGB reduces opioid requirements and post‐operative pain after orthotopic liver transplantation (OLT). Outcomes included the mean morphine milligram equivalents used; the proportion of patients with no pain documented; and the maximum level of pain documented within the first 24h and in the 24‐72h following OLT. A total of 44 patients received PGB vs 57 who received standard of care. Baseline demographics were comparable between groups. Patients who received PGB required 70% and 54% less opioids within the first 24h and subsequent 24‐72h post‐OLT, respectively ( p ‐values < .001). In the first 24h post‐OLT, there were more patients with no documented pain, and fewer with severe pain in the PGB group, but these were not significant. A greater proportion in the PGB group reported a maximum of mild pain ( p = .039). This study demonstrated that a single dose of pre‐operative PGB significantly reduced opioid use in the first 72 h after OLT. Larger studies will help determine the safety and efficacy of PGB in this setting.